Sea-level change and demography during the last glacial termination and early Holocene across the Australian continent. (15th February 2018) - Williams, Alan N.; Ulm, Sean; Sapienza, Tom; Lewis, Stephen; Turney, Chris S.M.
Abstract: Future changes in sea-level are projected to have significant environmental and social impacts, but we have limited understanding of comparable rates of change in the past. Using comprehensive palaeoenvironmental and archaeological datasets, we report the first quantitative model of the timing, spatial extent and pace of sea-level change in the Sahul region between 35-8 ka, and explore its effects on hunter-gatherer populations. Results show that the continental landmass (excluding New Guinea) increased to 9.80 million km 2 during the Last Glacial Maximum (LGM), before a reduction of 2.12 million km 2 (or ∼21.6%) to the early Holocene (8 ka). Almost 90% of this inundation occurs during and immediately following Meltwater Pulse (MWP) 1a between 14.6 and 8 ka. The location of coastlines changed on average by 139 km between the LGM and early Holocene, with some areas >300 km, and at a rate of up to 23.7 m per year (∼0.6 km land lost every 25-year generation). Spatially, inundation was highly variable, with greatest impacts across the northern half of Australia, while large parts of the east, south and west coastal margins were relatively unaffected. Hunter-gatherer populations remained low throughout (<30, 000), but following MWP1a, increasing archaeological use of the landscape, comparable to a four-fold increase in populations, and indicative of large-scale migration away from inundated regions (notably the Bass Strait) are evident. Increasing population density resulting from MWP1a (from 1/655 km 2 to 1/71 km 2 ) may be implicated in the development of large and complex societies later in the Holocene. Our data support the hypothesis that late Pleistocene coastal populations were low, with use of coastal resources embedded in broad-ranging foraging strategies, and which would have been severely disrupted in some regions and at some time periods by sea-level change outpacing tolerances of mangals and other near-shore ecological communities. Highlights: Investigation of scale, pace and human impacts of post-glacial sea-level change. Presents continental-scale consensus sea-level curve for Sahul between 35-8 ka. Demonstrates some 2.12 million km 2 (∼21.6%) of land lost, notably during MWP-1a. Coastlines changed on average by 139 km, and at a rate of up to ∼23.7 m per year. Populations low, but likely severely disrupted, and led to new configurations.